Employer Self-Insurance Decisions and the Implications of the Patient Protection and Affordable Care Act as Modified by the Health Care and Education Reconciliation Act of 2010 (ACA) - Eibner, Christine (RAND Corporation, 2011)
This report examines incentives for small firms to self-insure resulting from the Patient Protection and Affordable Care Act as amended by the Health Care and Education Reconciliation Act of 2010 (ACA) and considers the consequences of self-insurance for health plan enrollees. The study also uses the COMPARE microsimulation model to estimate how ACA will influence decisions to self-insure.